ChemInform Abstract: Friedlaender Annulation: Scope and Limitations of Metal Salt Lewis Acid Catalysts in Selectivity Control for the Synthesis of Functionalized Quinolines. Issue 14 (March 2016) - Tanwar, Babita; Kumar, Dinesh; Kumar, Asim; Ansari, Md. Imam; Qadri, Mohammad Mohsin; Vaja, Maulikkumar D.; Singh, Madhulika; Chakraborti, Asit K.
Abstract: Various functionalized quinolines are synthesized by condensation of 2‐aminobenzophenones (I) with β‐ketoesters, β‐diketones or ketones using In(OTf)3 as a very effective catalyst under solvent‐free conditions.